Fifty Glorious Years of NCERT in Guidance and Counselling - Joneja, Gursharan Kaur (JOURNAL OF INDIAN EDUCATION, 2012)
NCERT is the only nodal agency at the national level which has contributed to the field of guidance and counselling consistently, and over the last 50 years. While celebrating the Golden Jubilee year of NCERT, golden jubilee of guidance and counselling work at NCERT legitimately comes to mind. The Department of Educational Psychology and Foundations of Education of NCERT (name changed at different points of time) had been engaged in professional work in guidance and counselling extensively since its inception, or even much before in Central Bureau of Educational and Vocational Guidance (CBEVG) which was established as early as in 1954, and later on merged with NCERT in 1961. This way it is one of the oldest and primary thrust area in which NCERT continues to be engaged till today. The Golden Jubilee year is the time for introspection, reflection on its achievements and future challenges.